Citizens' confidence in government and inefficient public spending : is there a trust trap? - Rodrigues, Eduardo de Sá Fortes Leitão (2021)
The concept of trust is present in the most different areas of scientific knowledge. Associated with moral and philosophical perspectives, it influences the reputation of public institutions, and interferes with economic performance and welfare. Thus, trust is a complex interpersonal and organizational concept but closely linked to social capital, greasing the wheels of relationships and interaction between agents and public institutions. This article aims to assess the effects of inefficient/unproductive government spending on public trust and whether there is evidence of a trust trap. To investigate these effects, we use dynamic regression models and the Generalized Method of Moments (GMM) approach for panel models of 43 (2006-2019) and 33 (2006-2017) developed and developing countries. To further the investigation, we run panel vector autoregression (PVAR) models with the largest sample (43 countries). Our paper focuses on the response of trust in government to the effect of inefficient public spending and income inequality (GINI index). Moreover, we investigate whether the government's high level of inefficiency interferes with this relationship and whether there is evidence of a trust trap. The findings point to significant adverse effects of inefficient public spending on public trust, providing empirical support, and confirming the assumptions of some theoretical works. Our models indicate a threshold in the relationship between trust and inefficient government spending, that is, a trust trap. In short, to a certain extent, it is possible to regain trust by reducing the inefficiency of public spending. However, after this threshold, the recovery of trust requires a greater effort on the part of governments.